2001
DOI: 10.4049/jimmunol.167.7.3626
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Nuclear Import and Export That Control the Subcellular Localization of Class II Transactivator

Abstract: The presence of the class II transactivator (CIITA) activates the transcription of all MHC class II genes. Previously, we reported that deletion of a carboxyl-terminal nuclear localization signal (NLS) results in the cytoplasmic localization of CIITA and one form of the type II bare lymphocyte syndrome. However, further sequential carboxyl-terminal deletions of CIITA resulted in mutant forms of the protein that localized predominantly to the nucleus, suggesting the presence of one or more additional NLS in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
70
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 72 publications
7
70
0
Order By: Relevance
“…Protein translocation from cytoplasm into nucleus is dependent on the presence of a nuclear localization signal (NLS) within the protein [45]. Constitutive nuclear localization of mammalian IRF-1 has been confirmed, and its NLS has been localized to a region C-terminal beside the DBD, spanning amino acids 117-141 [46].…”
Section: Discussionmentioning
confidence: 96%
“…Protein translocation from cytoplasm into nucleus is dependent on the presence of a nuclear localization signal (NLS) within the protein [45]. Constitutive nuclear localization of mammalian IRF-1 has been confirmed, and its NLS has been localized to a region C-terminal beside the DBD, spanning amino acids 117-141 [46].…”
Section: Discussionmentioning
confidence: 96%
“…This dual subcellular distribution is the net result of multiple nuclear import and nuclear export signals (53,(60)(61)(62)(63)(64)(65). Because Tax-2 activates the viral promoter in the nucleus, it is likely that CIITA inhibits Tax-2 at the nuclear level.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our study shows that like other CIITA, DC-CIITA localizes to cytoplasm and nucleus but not mitochondria (unpublished data). It has been reported that the C-terminal two-third of the CIITA protein contains at least two nuclear-localization signals (NLS2 and NLS3) (Cressman et al, 2001). Thus, it is possible that these signals in the full length DC-CIITA might cover mitochondria targeting signal in the CARD-like domain.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, our study shows that a novel DC-CIITA splicing isoform, DC-CASPIC, regulates the expression of NOS2 and NO synthesis in the maturing DC. This is an efficient mechanism where transcription via the type-1 CIITA promoter produces two splice-isoforms of mRNA encoding for two proteins (DC-CIITA and DC-CASPIC) with distinct functions in the maturing DC, where DC-CIITA preferentially localizes to nucleus (Cressman et al, 2001) and regulates transcription of MHC genes while DC-CASPIC localizes to mitochondrial organelle (as well as cytoplasm) and regulates NO synthesis. -202), and Jurkat T cell lymphocyte cell line (TIB-152) were obtained from the American Type Culture Collection (ATCC, Manassas, VA, USA).…”
Section: Discussionmentioning
confidence: 99%